Agroecologia e agricultura orgânica na perspectiva dos atores sociais no estado do Ceará - Mora, Anyi Elizabeth Morales (2018)
This research is embedded in the area of Agroecology and aims to systematize the perceptions about agroecological and organic agriculture of peasants, technicians, managers and academics, who perform their roles on areas related to agriculture and rural sustainable development in the state of Ceará. The research is part of the creation of the Nucleus on Agroecology and Ecological Economics that will belong to the Agricultural Sciences Center of the Federal University of Ceará. The study is based on a descriptive methodological design, in which priority was given to semi-structured interview techniques and bibliographic review to facilitate the perceptions’ processing, systematization and analysis. Two interview formats were developed: one for peasants and one for the other actors. A non-probabilistic sampling known as “snowball” was used to select the interview subjects. 43 interviews were conducted during the period between February and March 2018, with the intermediation of several organizations, primarily from the Cáritas Arquidiocesana de Fortaleza and the Centro de Estudos do Trabalho e de Assessoria ao Trabalhador - CETRA. The participants are mainly agroecological peasants (16), organic peasants (8), Technical Assistance and Rural Extension (TARE) technicians (6), development project managers (5) and scholars (8). The group of interviewees is made up of 15 women and 28 men, aging from 24 to 63 years. Social actors’ educational level varies, mainly within peasants, indicating that few of them have finished high school and only four possess higher education studies (technical and university level). Among technicians, one has technical studies and the others have obtained a superior education at a university level. Managers and scholars are graduates. As an analysis method was employed the content analysis, due to the research’s nature, which sought to understand how the actors organize and elaborate their ideas and perceptions on Agroecology, organic agriculture and rural sustainability. Thematic categories and subcategories emerging from the analysis were organized into five major thematic blocks: Sustainable Agriculture, Living with the Semi-Arid, Knowledge Construction, Favourable Public Policies and Family and Community Economy. It was possible to deepen the understanding of the relationship between Agroecology and Living with the Semi-Arid, since both are sustainability paradigms based on the territorial complexity, water management, the promotion of contextualized sustainable agriculture forms and the solidarity economy’s creation and consolidation, the latter as a strategy to reclaim the peasantry’s position as the central subjects of the sustainable rural development model. Subsequently, the study made it possible to characterize the sustainability social-environmental rationality in the context of the semi-arid region of Ceará, by showing that social actors manifest an understanding of the agroecosystems complexity and, therefore, the need to adapt agricultural practices to Brazilian Semiarid conditions. For social actors, Agroecology is a science, a practice, a way of thinking and feeling. In other words, social actors perceive the multidimensionality of Agroecology, especially farmers and technicians. For the organic agriculture, it was difficult for farmers to distinguish it from Agroecology. This type of agriculture is recognized primarily as a form of input-substitution agriculture, geared to meet the demand of a niche market. It is worth noting that the majority of farmers stated that they did not know the concept of Living with the Semi-Arid, even though they follow the principles of this sustainability paradigm. In relation to public policies that favour agroecological and organic agriculture and guide their action, in the four groups there was little knowledge about the policies and understanding of their functioning and articulation. It can be inferred, firstly, that there is a lack of policies positioning on social actors and the limitations of their implementation are closely related to the federal and state public management style prevailing in Brazil. Secondly, greater resources are made available for agribusiness policies. These factors affect the appropriation, application and adequate operationalization of agroecological principles, fundamentals and guidelines in the public policies implementation and the sustainable development model positioning for food sovereignty in Brazil. On the other hand, the actors indicate their concerns about the agricultural future due to the persistence of conventional agricultural hegemony, rural youth unemployment, rural-urban exodus and distortion of the principles of sustainability in organic production. Nonetheless, these actors have expressed a positive expectation regarding the transition from conventional agriculture to Agroecology. In this sense, the research indirectly managed to portray the involved social actors’ ideas with regard to the expected rural sustainable development model. Likewise, the study revealed there is a strong need to promote Agroecology in the Brazilian Semiarid, based on the knowledge construction, adequate existing public policies implementation and the strengthening of current institutional and social arrangements and the creation of new ones that underpin these new forms of sustainable agriculture. Certainly, deepening the knowledge about family farmers, the communities that support them and the institutions that support them, have a positive impact on the policies, programs and projects relating to rural development.